Deceleration observed in the coronal mass ejection event of July 25, 1999 - N. J. Schuch; F. L. Guarnieri; E. Echer; L. E. A. Vieira; A. L. C. de Gonzalez; W. D. Gonzalez; G. Stenborg; R. Schwenn; A. Dal Lago (Geofísica Internacional, 2004)
We present height-time diagrams of the halo coronal mass ejection observed on July 25th (1999) from the Large Angle and Spectroscopic Coronagraph (LASCO), on board of the Solar and Heliopheric Observatory (SOHO) able to observe the solar corona from 2 to 32 solar radii. We used a technique in which the LASCO images are divided in angular slices and placed side by side at different observation times, thus producing height-time diagrams. We identify a small deceleration of the July 25th halo CME around the south pole of the sun.